The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4103/0019-5359.40579
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urticaria and <i>Helicobacter pylori</i>

Abstract: BACKGROUND: Helicobacter pylori (HP) have recently emerged as a novel eliciting factor for chronic urticaria (CU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 7 publications
2
34
1
1
Order By: Relevance
“…The demographic profile of the 150 patients in this study corroborates with descriptions in the dermatology literature [1][2][3]. An etiopathogenetic link between H. pylori infection and chronic urticaria and possible improvements after its eradication has been demonstrated.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The demographic profile of the 150 patients in this study corroborates with descriptions in the dermatology literature [1][2][3]. An etiopathogenetic link between H. pylori infection and chronic urticaria and possible improvements after its eradication has been demonstrated.…”
Section: Discussionsupporting
confidence: 70%
“…However, a greater number (96 vs. 15) of patients with positive test results had a significantly higher (p < 0.05) mean number of systemic symptoms than patients with negative results. Furthermore, the prevalence of H. pylori-associated gastrointestinal symptoms remains variable, from being symptomatic to the complete absence of symptoms [2,8,10,28]. In their 57% urticaria patients with positive H. pylori, Abdou et al [10] reported no gastric symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies from various groups indicate that H. pylori is associated with a variety of extragastric disorders such as type 2 diabetes mellitus [7,8], dermatological disorders such as scleroderma [9], rosacea [10], psoriasis [11], chronic idiopathic urticaria [12,13], primary Raynaud's phenomenon [14,15], migraine [16], Guillain-Barre syndrome [17], acute inflammatory demyelinating polyradiculoneuropathy [18], chronic idiopathic thrombocytopenic purpura [19,20], cardiovascular risk factors such as acute coronary ischemia [21] and chronic recurrent abdominal pain [22][23][24]. The cause of vitamin B 12 deficiency, iron deficiency, and vitamin B 12 /iron deficiency anemia in children has also been linked to H. pylori infection [25][26][27][28].…”
Section: Association Of H Pylori With Other Diseasesmentioning
confidence: 99%